ADMNISTRASI MANAGEMENT PERTANDINGAN KEPELATIHAN OLAHRAGA - Muhammad Nurdzaky Alfatih; Rassya Nayla Ruliansyah; Refina Jiska Adelia; Hotma K Gultom; Alfin Siregar; Siti Rahima Gultom; Ibrahim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of event administration and management in sports coaching and its impact on athlete performance and satisfaction, the effectiveness of coaching programs, and spectator satisfaction. The study employs a literature review method by examining various scientific sources, including books, journals, articles, and relevant previous research findings. Data were analyzed through a process of identification, evaluation, and synthesis of research findings related to sports administration and management. The results indicate that effective event management contributes to improved athlete performance through optimal management of facilities, logistics, communication, and psychological support. Additionally, there is a positive and significant relationship between event management and athlete satisfaction, with a correlation coefficient of 0.483 and a significance level of 0.000. Well-planned, systematic training programs supported by continuous evaluation have also been proven to enhance players’ tactical skills. On the other hand, good match administration has a positive impact on spectator satisfaction through easy ticket access, facility quality, security, and service during the match. Thus, professional sports administration and event management are key factors in ensuring the success of sporting events and enhancing the experience for all parties involved.